2003
DOI: 10.1103/physrevlett.91.130602
|View full text |Cite
|
Sign up to set email alerts
|

Quantum to Classical Transition for Random Walks

Abstract: We look at two possible routes to classical behavior for the discrete quantum random walk on the integers: decoherence in the quantum "coin" which drives the walk, or the use of higher-dimensional (or multiple) coins to dilute the effects of interference. We use the position variance as an indicator of classical behavior and find analytical expressions for this in the long-time limit; we see that the multicoin walk retains the "quantum" quadratic growth of the variance except in the limit of a new coin for eve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
228
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(239 citation statements)
references
References 8 publications
8
228
3
Order By: Relevance
“…Only if a new coin is used for every step of the walk does it become equivalent to the classical random walk. This is in contrast with the behaviour obtained by decohering the coin (Brun et al 2003a), which always results in classical limiting behaviour, as pointed out in Brun et al (2003b). Classical behaviour is thus associated with an environment so large that one never comes close to the Poincaré recurrence time over the timescales considered.…”
Section: Multiple Coins In the Walk On The Linecontrasting
confidence: 46%
See 2 more Smart Citations
“…Only if a new coin is used for every step of the walk does it become equivalent to the classical random walk. This is in contrast with the behaviour obtained by decohering the coin (Brun et al 2003a), which always results in classical limiting behaviour, as pointed out in Brun et al (2003b). Classical behaviour is thus associated with an environment so large that one never comes close to the Poincaré recurrence time over the timescales considered.…”
Section: Multiple Coins In the Walk On The Linecontrasting
confidence: 46%
“…This can then be integrated by parts. Brun et al (2003b) chose pure dephasing for the form of the decoherence on the coin, so the coin projectors in equation (55) are…”
Section: Dephasing the Coin In The Walk On The Linementioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the opportunity to achieve exponential speedups over classical techniques by harnessing entanglement between densely encoded states in a quantum computer. Quantum walks have been the focus of several recent studies (see for example, [1,2,3,4,5]), with particular interest in possible algorithmic applications of the walks [6,7,8,9,10]. A few such algorithms have already been developed, perhaps the most notable being the 'glued trees' algorithm developed by Childs et al [6], in which quantum walks are shown to traverse a family of graphs exponentially faster than any possible classical algorithm, given a certain quantum oracle.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of quantum walks of both types has been studied in detail for walks on an infinite linefor the continuous-time case in Refs. [7,11,12] and for the discrete-time case in [13,14,15,16,17]. There has also been considerable work on other regular graphs.…”
Section: Introductionmentioning
confidence: 99%